RESTORASI TAMAN BEJI SAPTA RESI SEBAGAI WISATA RELIGI DI DESA ADAT SAMUAN: PERSEPSI MASYARAKAT DAN IMPLIKASINYA - I Made Putra Aryana (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
This article aims to describe community perceptions and the implications of the restoration of Taman Beji Sapta Resi. Restoration, namely returning the beji function to its original function. This article is the result of research conducted using data collection methods in the form of observation, interviews, literature study and documentation, with qualitative descriptive data analysis. The taman beji restoration was carried out because of knowledge of the existence of beji and its function was restored as beji which has a natural panorama of economic value. The potential for opening Taman Beji Sapta Resi as a tourist attraction includes: natural conditions around the Taman Beji Sapta Resi, development of tourism facilities, and management of tourist attractions. The public's perception of the opening of Taman Beji Sapta Resi as a place of religious tourism is efficiency in the implementation of the Masucian Pratima procession, the existence of a place to increase self-purity, open employment opportunities for the surrounding community so that it has an impact on community welfare and increases the income of village funds. So that the impact will be in the form of economic, social, cultural and environmental impacts.